2004
DOI: 10.1017/s1049023x00001990
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Use of Aspirin Rarely Is Associated with Adverse Events

Abstract: Introduction: Aspirin is commonly administered for acute coronary syndromes in the prehospital setting. Few studies have addressed the incidence of adverse effects associated with prehospital administration of aspirin. Objective: To determine the incidence of adverse events following the administration of aspirin by prehospital personnel. Methods: Multi-center, retrospective, case series that involved all patients who received aspirin in the prehospital setting from (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Other possible reasons for lower prevalence of aspirin administration could include absolute contraindications to aspirin such as a history of an anaphylactic response to aspirin or relative contraindications such as gastrointestinal bleed or kidney disease. However, prehospital use of aspirin is safe and rarely associated with adverse events 16. True aspirin intolerance or ‘allergy’ is estimated at only 2% to 3% of the general population 17.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible reasons for lower prevalence of aspirin administration could include absolute contraindications to aspirin such as a history of an anaphylactic response to aspirin or relative contraindications such as gastrointestinal bleed or kidney disease. However, prehospital use of aspirin is safe and rarely associated with adverse events 16. True aspirin intolerance or ‘allergy’ is estimated at only 2% to 3% of the general population 17.…”
Section: Discussionmentioning
confidence: 99%
“…283 Two other studies showed that the potential benefit from early aspirin administration outweighs potential harm (LOE 1). 284,285 Treatment Recommendations Despite limited direct evidence to support or refute the practice, it may be reasonable to consider EMS or dispatcherguided bystander aspirin administration, provided an adequate history to exclude a true allergy or a bleeding disorder, can be obtained. 293 was neutral in demonstrating benefit in the combined event rate of cardiovascular mortality, nonfatal infarction, nonfatal stroke, and overall mortality.…”
mentioning
confidence: 99%
“…Aspirin is recommended in the CPGs as it is safe, inexpensive, easy to administer and has significant benefits in reducing mortality and other vascular complications following myocardial infarction 7 8. A multicentre study of 922 patients with acute myocardial infarction showed that patients who received aspirin before arrival at hospital had a significantly lower mortality rate than those given aspirin following admission, both at 7 days (2.4% vs 7.3%, respectively) and at 30 days (4.9% vs 11.1%, respectively), as well as a lower incidence of serious complications including pulmonary oedema, cardiogenic shock and cardiac arrest 9…”
mentioning
confidence: 99%